Navigating healthcare systems before and after resettlement: Exploring experiences and recommendations for improvement from the perspectives of a Bhutanese refugee community - Manisha Salinas; David Matarrita-Cascante; Juan L. Salinas; James N. Burdine (Elsevier, 2021)
Background: Though refugees often survive in refugee camps for many years, little is known about the impact of their interactions within the healthcare system during that time and how it may affect current concerns with the healthcare system after resettlement. Guiding our analysis was the Community Health Development model, which emphasizes the importance of understanding the impact of historical experiences on a community's health to identify specific current health needs, and plan solutions alongside the community to address and improve health concerns. Objective: To better understand the healthcare system related experiences of Bhutanese refugees before and after resettlement, and describe potential solutions based on their perspectives to improve their health status. Methods: This study used an explorative qualitative research design. Four focus group discussions were conducted with 40 female participants to examine their experiences within the healthcare system in Nepal (e.g. before resettlement) and the US (after resettlement). Focus group data were audio-recorded, translated, coded, and reported based on qualitative thematic analysis. Results: Findings revealed that Bhutanese refugees were mistreated in the Nepalese healthcare system, often neglected from healthcare access and services because of their refugee status. Upon arrival to the United States after resettlement, study participants also reported experiencing challenges within the US health care system including cultural and linguistic barriers when interacting with medical interpreters during visits with their providers, as well as having inadequate time during the visit to fully express their concerns. Respondents' recommendations to improve their overall health centered on their experiences with the US health care system including initiatives developing leadership skills for building community capacity towards advocating for the refuges, while increasing access to external resources. Conclusion: The result of this study outlines an account of Bhutanese refugees' experiences and recommendations for improving their community's health based on such past experiences and their current needs. These findings provide a starting point for future research with underserved refugee migrant groups and indicate a need for health programs to be historically and culturally sensitive in order to be more effective. Further, the understanding of refugees' collective history should inform the development of collaborative interventions with community members in order to be effective.